A Note on Vulnerability : Findings from Moving Out of Poverty - Dudwick, Nora (World Bank, Washington, DC, 2012)
Poverty studies typically focus on people who live below the poverty line. Few studies have examined how people are able to not only move out of but also stay out of poverty. The fifteen, country study, moving out of poverty: success from the bottom up, by Deepa Narayan, Lant Pritchett, and Soumya Kapoor, is one of the few large-scale comparative research attempts to analyze mobility out of poverty rather than poverty alone. The study focused largely on rural communities over a 10-year period between 1995 and 2005, when developing countries exhibited overall relatively strong growth.